Β‐caryophyllene oxide inhibits constitutive and inducible STAT3 signaling pathway through induction of the SHP‐1 protein tyrosine phosphatase. Issue 10 (13th June 2013) - Kim, Chulwon; Cho, Somi K.; Kapoor, Shweta; Kumar, Ansu; Vali, Shireen; Abbasi, Taher; Kim, Sung‐Hoon; Sethi, Gautam; Ahn, Kwang Seok
Abstract Constitutive activation of STAT3 is frequently observed and closely linked with proliferation, survival, invasion, metastasis and angiogenesis in tumor cells. In the present study, we investigated whether β‐caryophyllene oxide (CPO), a sesquiterpene isolated primarily from the essential oils of medicinal plants such as guava (Psidium guajava), and oregano (Origanum vulgare L.), can mediate its effect through interference with the STAT3 activation pathway in cancer cells. The effect of CPO on STAT3 activation, associated protein kinases and phosphatase, STAT3‐regulated gene products and apoptosis was investigated using both functional proteomics tumor pathway technology platform and different tumor cell lines. We found that CPO suppressed constitutive STAT3 activation in multiple myeloma (MM), breast and prostate cancer cell lines, with a significant dose‐ and time‐dependent effects observed in MM cells. The suppression was mediated through the inhibition of activation of upstream kinases c‐Src and JAK1/2. Also, vanadate treatment reversed CPO‐induced down‐regulation of STAT3, suggesting the involvement of a tyrosine phosphatase. Indeed, we found that CPO induced the expression of tyrosine phosphatase SHP‐1 that correlated with the down‐regulation of constitutive STAT3 activation. Interestingly, deletion of SHP‐1 gene by siRNA abolished the ability of CPO to inhibit STAT3 activation. The inhibition of STAT3 activation by CPO inhibited proliferation, induced apoptosis and abrogated the invasive potential of tumor cells. Our results suggest for the first time that CPO is a novel blocker of STAT3 signaling cascade and thus has an enormous potential for the treatment of various cancers harboring constitutively activated STAT3. © 2013 Wiley Periodicals, Inc.